Forgotten Industrial Heritage: The Cement Factory from La Granja d’Escarp - Judit Ramírez-Casas; Ricardo Gómez-Val; Felipe Buill; Belén González-Sánchez; Antonia Navarro Ezquerra (Buildings, 2025)
In the municipality of La Granja d’Escarp, for over thirty years, an important natural cement factory was in operation. In 1876, the Girona family, who were businessmen and bankers from Barcelona, opened the factory with modern industrial facilities. It included kilns, mills, and crushers, alongside warehouses, a small railway for internal transportation of the various materials used, and even a housing area for workers. The neighboring Ebro River allowed distribution by river transport at first. Later, with the use of railways, transport to consumption points was possible. This industrial complex became a center of significant importance in Catalonia in the production of cement, which was used for building hydraulic and civil works. During the first decade of the twentieth century, the factory stopped its activity and the facilities were abandoned. Nowadays, this industrial heritage site is in a state of neglect, without any kind of protection or maintenance. In turn, this has caused the collapse of some buildings in recent times and the loss of historical value of the architectural ensemble. We have carried out initial geomatic research, which has highlighted the constructive properties of the kilns. We have also tested five samples from different buildings using XRD and TGA/DSC, which showed the use of lime mortars in their construction. This is the first study to be carried out at this site, with the aim of showing the historical importance of the ensemble. The goal of the study was to highlight the value of this industrial heritage site and illustrate that it was once a pioneer in the production of natural cement and a driving force for Catalonia.